Inovasi Ecollabo8 pada Sampah Plastik untuk Kebutuhan Interior - Sahita, Cita Luvi; Setyoningrum, Yunita (Waca Cipta Ruang, 2023)
Plastic waste is one of the biggest causes of environmental pollution, especially soil and sea pollution. Proper management is needed to reduce the impact of plastic waste on the environment. Meanwhile, in Indonesia, waste management has not been able to reduce the impact of plastic waste by recycling and turning it into something more valuable. Ecollabo8 impact of plastic waste itself. It is necessary to process plastic waste that can be reused and increase the value of recycled products. Ecollabo8 is a community that aims to recycle plastic into interior materials, such as furniture, wall coverings, or materials for interior aesthetic elements. The purpose of this research is to provide information and references related to the processing of plastic waste from various categories so that it can become an interior material innovation by Ecollabo8. The research method used is the netnographic method by observing the activities and culture of Ecollabo8 through social media and online documentation.